Recursos didácticos tecnológicos, para el logro de aprendizajes significativos en Biología. Año lectivo 2021-2022 - Uchuari Macas, Karina Stefania (2022)
Technological didactic resources allow to dynamize the classroom process and therefore improve the quality of the teaching and learning process. The objective of this Curriculum Integration research was to promote the achievement of significant learning in students, through the application of technological didactic resources, which allow to dynamize the teaching and learning process in the Biology subject of the first year of Bachillerato General Unificado in “La Dolorosa” High School; 2021-2022 school year; for this, the guidelines of a qualitative research were considered; due to the need to identify the characteristics of the context before and after the intervention was carried out. In addition, it is considered as a participatory action research; since, from the diagnosis of the problem to its solution, the students, the main components of the research, actively collaborated with the researcher to generate solutions. The intervention was carried out in a certain period of time and therefore corresponds to a cross-sectional investigation. According to the results obtained through the evaluation instruments (structured base test) and applied research (survey and interview), it was possible to show that the implementation of technological didactic resources such as: videos, 3D material, slides and conceptual maps in online programs, in the teaching-learning process of the Biology subject, aroused the interest of the students to participate in the development of the classes, which generated significant changes in the learning that each one of them built. Therefore, it is determined that the application of technological and didactic resources dynamizes the teaching and learning process in the biology subject and with it, the achievement of significant learning in students is enhanced, which is reflected in the improvement of their grades. Keywords: motivation, classroom process, teaching-learning process, constructivism.